Cost-Effectiveness of Crisis Resolution Home Treatment for Managing Acute Psychiatric Crises in Southern Switzerland - Emiliano Soldini; Maddalena Alippi; Salvatore Maione; Zefiro Benedetto Mellacqua; Luca Crivelli (International Journal of Public Health)
ObjectivesThis study aimed at providing the first formal cost-effectiveness evaluation of Crisis Resolution Home Treatment (CRHT) compared to hospitalization for the management of acute psychiatric crises in Switzerland.MethodsIntervention (CRHT) and control (hospital) groups were formed based on patients’ place of residence according to a quasi-experimental design. Patients were followed starting from an acute episode of care until 2 years after discharge. Effectiveness measures were variation of psychiatric symptoms between admission and discharge and number of non-readmission days. Direct costs were obtained from the Cantonal Psychiatric Clinic and patients’ health insurance companies. Indirect costs were estimated based on sick leave certificates. Bootstrap resampling procedures and Cost-Effectiveness Acceptability Curves were used to assess cost differences between groups and cost-effectiveness.ResultsCRHT resulted generally less costly than hospitalization. In the treatment phase, cost-effectiveness depended on the type of psychiatric symptoms considered, while CRHT resulted highly cost-effective in the follow-up phase.ConclusionCRHT can be a cost-effective alternative to hospitalization for managing acute psychiatric crises in Ticino. Further research is needed to explore patients’ conditions and characteristics associated with cost-effectiveness.